Nivel de conocimiento y prácticas de prevención sobre dengue en los habitantes del barrio Trapichillo cantón Catamayo provincia de Loja - Aguilar Jiménez, Daniel Alexander (2023)
Dengue is a disease that affects people of all ages, with symptoms that vary from a mild fever to a disabling fever, intense headache, retro-ocular pain, pain in muscles and joints; it can progress to severe forms, including shock and/or severe organ damage. The objective of the research is to determine the level of knowledge and prevention practices about dengue, in the inhabitants of the Trapichillo neighborhood, Catamayo canton, Loja province. The study was quantitative, descriptive and cross-sectional, with a sample of 276 inhabitants; ethical considerations and inclusion criteria were taken into account, a survey validated by Cronbach's alpha reliability test was applied. For data processing, the statistical package SPSS version 26 is extracted and the results are represented by means of tables; among these, it was found that 45.3% of the respondents have a partially adequate level of knowledge about dengue, 40.9% an inadequate level of knowledge and only 13.8% have an adequate level of knowledge. Regarding the prevention practices carried out by the inhabitants, 64% are inadequate and 36% are adequate. Therefore, it is concluded that the majority of the inhabitants of the Trapichillo neighborhood do not have sufficient knowledge or prevention practices to control or avoid the disease